LONG-TERM FOLLOW-UP OF ADULT PATIENTS WITH IDIOPATHIC THROMBOCYTOPENIC PURPURA AFTER SPLENECTOMY - Pavkovic M; Trpkovska-Terzieva S; Latifi A; Karanfilski O; Cevreska L; Stojanovic A (My University, 2011)
Background: Idiopathic thrombocytopenic purpura (ITP) is an autoimmune disease characterized by isolated thrombocytopenia and the absence of any underlying cause for thrombocytopenia. Corticosteroids are the standard first line treatment for patients with symptomatic disease, but in many cases, steroid tapering or withdrawal is followed by a decrease of platelet count and the need for additional treatment. Splenectomy is still the standard salvage therapy in cases refractory to corticosteroid therapy. Aim: The aim of this study was to evaluate the long-term outcome of splenectomized patients with ITP. Materials and Methods: We retrospectively analyzed medical records of 38 patients with ITP that underwent splenectomy after first-line steroid treatment. All patients were followed for at least one year. Results: According to the results at the time of the last control, 28 patients had complete response (CR), but from those 28 patients only 22(58%) were without therapy and 6(22%) were receiving prednisone, azathioprine or both. These results indicate that only 22/38(58%) of patients had long-lasting CR without therapy, 12 patients (31%) were receiving therapy and 4 patients (11%) had partial response without therapy. Conclusion: In conclusion, splenectomy may be considered as safe and effective treatment for patients with ITP who failed to respond to firs-line treatment with corticosteroids.
Keywords: idiopathic thrombocytopenic purpura; splenectomy; follow-up; response rate